2016
DOI: 10.1038/nrdp.2016.59
|View full text |Cite
|
Sign up to set email alerts
|

Infective endocarditis

Abstract: Infective endocarditis (IE) is a rare, life-threatening disease that has long-lasting effects even among patients who survive and are cured. IE disproportionately affects those with underlying structural heart disease and is increasingly associated with healthcare contact, particularly in patients who have intravascular prosthetic material. In the setting of bacteraemia with a pathogenic organism, an infected vegetation may form as the end result of complex interactions between invading microorganisms and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
321
2
35

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 326 publications
(364 citation statements)
references
References 218 publications
(224 reference statements)
6
321
2
35
Order By: Relevance
“…Several infections, including IE, cause positive ANCA tests by indirect immunofluorescence but negative ELISA testing. Our patient presented with positive p-ANCA (by ELISA); thus, this finding was most probable because of an AAV 1,11 . Glomerulonephritis is the most frequent histological finding in this type of vasculitis; however, some cases may consist of interstitial nephritis without glomerular involvement, as shown in this patient 12 .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Several infections, including IE, cause positive ANCA tests by indirect immunofluorescence but negative ELISA testing. Our patient presented with positive p-ANCA (by ELISA); thus, this finding was most probable because of an AAV 1,11 . Glomerulonephritis is the most frequent histological finding in this type of vasculitis; however, some cases may consist of interstitial nephritis without glomerular involvement, as shown in this patient 12 .…”
Section: Discussionmentioning
confidence: 94%
“…Additionally, a few Bartonella spp. have been identified as causes of endocarditis, with Bartonella quintana and Bartonella henselae being the most common 1 . Bartonella bacilliformis, the etiologic agent of Carrion's disease (CD), has also been reported as a cause of endocarditis in a pediatric patient with a history of right ventricular-coronary artery fistula 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies identified several candidate innate immunity biomarkers that were independently associated with mortality and prolonged SAB, supporting the utility of biomarkers to distinguish patients prone to developing severe disease . Such information would be particularly beneficial in guiding diagnostic work‐up of patients at increased risk of S. aureus infective endocarditis (IE), a disease that even with the best available treatments has contemporary in‐hospital mortality rates ranging from 25 to 46% …”
Section: Introductionmentioning
confidence: 93%
“…1,[4][5][6][7] Such information would be particularly beneficial in guiding diagnostic work-up of patients at increased risk of S. aureus infective endocarditis (IE), a disease that even with the best available treatments has contemporary in-hospital mortality rates ranging from 25 to 46%. [8][9][10] To investigate the contribution of the differential immune response to SAB disease severity, we previously identified biomarker profiles associated with mortality and persistent bacteraemia in a twophase case-control study of patients with complicated SAB. There, we evaluated a panel of 13 candidate biomarkers in patients with complicated SAB enriched for persistent bacteraemia and mortality and observed that high IL-17A, IL-10 and soluble E-selectin (sE-selectin) levels at presentation were prognostic for persistent bacteraemia, while high levels of IL-8 and CCL2 were prognostic for mortality.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, new microorganisms have been emerging with increasing incidence, especially affecting intracardiac devices [1]. The old term "bacterial endocarditis" has largely been replaced by the more accurate terms "infective" or "infectious" endocarditis, since infections caused by microorganisms other than bacteria are possible and not at all infrequent [2]. The reported incidence of infectious endocarditis in the general population is 3-10 episodes per 100,000 people per year, though IE is less common in the young and especially common in seniors between the ages of 70 and 80 years [3].…”
Section: Introductionmentioning
confidence: 99%